Large eddy simulation of dispersion of hazardous materials released from a fire accident around a cubical building - Vasilopoulos, Konstantinos; Lekakis, Ioannis; Sarris, Ioannis E.; Tsoutsanis, Panagiotis (Springer, 2021)
The turbulent smoke dispersion from a pool fire around a cubical building is studied using large eddy simulation at a high Reynolds number, corresponding to existing experimental measurements both in laboratory and field test scales. Emphasis of this work is on the smoke dispersion due to two different fuel pool fire accident scenarios, initiated behind the building. For the setup of fire in the first case, crude oil was used with a heat release rate of 7.8 MW, and in the second, diesel oil with a heat release rate of 13.5 MW. It is found that in both fire scenarios, the downstream extent of the toxic zone is approximately the same. This is explained in terms of the fact that the smoke concentration and dispersion are influenced mainly by the convective buoyant forces and the strong turbulence mixing processes within the wake zone of the building. It is suggested that wind is the dominating factor in these accident scenarios, which represent the conditions resulting in the highest toxicity levels.
Keywords: LES; smoke dispersion; fire accident; toxic zones